mer-[InCl3(C5D5N)3]2·C5D5N: A New d5-pyridine Derivative of Indium(III) Chloride Complex - Tuna, Ali; Papageorgiou, Anastassios; Peuronen, Anssi; Peljo, Pekka; Knör, Günther (Turkish Chemical Society - DergiPark, 2025)
In this study, we report the crystal structure of a meridional octahedral pyridine-indium(III) chloride adduct, mer-trichlorotris(d5-pyridine)indium(III)·0.5(d5-pyridine), InCl3(C5D5N)3·0.5(C5D5N), which exhibits an unreported molecule-to-solvent ratio compared to other substituted and unsubstituted pyridine-indium(III) chloride adducts described in earlier literature. The bonding characteristics of this d5-pyridine complex are compared to analogous complexes that have already been reported. Furthermore, the role of this metal complex in indium insertion into corrole ligands is discussed.